Exploiting Free‐Energy Minima to Design Novel EphA2 Protein–Protein Antagonists: From Simulation to Experiment and Return. Issue 24 (3rd May 2016) - Russo, Simonetta; Callegari, Donatella; Incerti, Matteo; Pala, Daniele; Giorgio, Carmine; Brunetti, Jlenia; Bracci, Luisa; Vicini, Paola; Barocelli, Elisabetta; Capoferri, Luigi; Rivara, Silvia; Tognolini, Massimiliano; et al.
Abstract: The free‐energy surface (FES) of protein–ligand binding contains information useful for drug design. Here we show how to exploit a free‐energy minimum of a protein‐ligand complex identified by metadynamics simulations to design a new EphA2 antagonist with improved inhibitory potency. Abstract : The free‐energy surface (FES) of protein–ligand binding contains information useful for drug design. A free‐energy minimum of a protein–ligand complex identified by metadynamics simulations can be exploited to design a new EphA2 antagonist with improved inhibitory potency.